Flake LABU KUNING (cucurbita moschata) DENGAN KADAR VITAMIN A TINGGI (Pumpkin (cucurbita moschata) flake with high-vitamin a content) - Latifah, Ir; Susilowati, Titi; Erlita, Tri Rini (REKAPANGAN, 2010)
Flake is a type of breakfast , ready meals  and golden brown with a crunchy texture. In general, flake were made from wheat flour or from starch tubers like tapioca starch. Pumpkin has  vitamin  A  and  high  fiber  content.  Therefore  flakes  may  be  added  starch  and  materials developers  Sodium  bicarbonate  (NaHCO3)  is  expected  to  assist  the  process  of  gelatinization perfectly  until the flakes produced  porous and crisp.This research aims to study the effect of the  proportion  of  pumpkin  and  tapioca  flour  with  the  addition  of  sodium  bicarbonate  to  the flakes  to  obtain  flake  with  acceptable  quality.  The  methods    are  factorial design which arranged completely randomized and each of two treatment combination was replicated three times. The first factor is the proportion of pumpkin flour: tapioca (60: 40: 65: 35: 70: 3;) g and the  second  factor  was  the  concentration  of  sodium  bicarbonate  (0.25,  0.50,  0.75)%.  The  best results  were  getted  with  the  proportion  of  pumpkin  flour:  tapioca  flour(65:  35)  g  with  the addition  of  0.50%  sodium  bicarbonate  to  produce  flakes  with  water  content  7.56%,  starch 43.23%, fiber 8.03%, β-carotene 33.74 μ g / g, 30.11% rehydration capacity and texture of 0.27  kg  /  cm,  while  the  method  of  ranking  organoleptic  texture  values  obtained  91  and  86 colors (highly preferred) and a sense of 71 (less preferable).Key word: Flakes, pumpkin, starch, tapioka, β karoten